Synthesis, Characterization, and BSLT Test of Pyrazoline and Pyrazole Compounds from Chalcone using Microwave Irradiation (Chimica et Natura Acta, 2023)
Pyrazole is an organic compound, classified as an alkaloid, featuring a heterocyclic five-membered ring structure composed of three carbon atoms and two adjacent nitrogen atoms, forming an endocyclic double bond. Pyrazole has various biological activities, such as antibacterial, anticanc er, antiinflammatory, antidepressantion, and antioxidant. Pyrazole 2-(5-(4-chlorophenil)-1-phenil-1H-pyrazole-3il)phenol (TFP-2OH-4Cl) was synthesized via oxidative aromatization reaction of pyrazoline 2-(5-(4-chlorophenil)-1-phenil-4,5-dihydro-1H-pyrazole-3-il)phenol (PF-2OH-4Cl) with glacial acetic acid. Chalcone, pyrazoline, and pyrazole were synthesized using the microwave at 180 W at 85oC. The purity of the compounds was monitored on TLC plates, melting point, and HPLC analysis. The structure of synthesized compounds was confirmed by UV, FTIR, HNMR, and HRMS spectroscopic analyses. The yields obtained from synthesizing 2OHA-4ClBD, PF-2OH-4Cl, and TFP-2OH-4Cl compounds were 63.49%, 64.35 %, and 40.42 %. The cytotoxic activity of chalcone, pyrazoline, and pyrazole was evaluated by Brine Shrimp Lethality Test (BSLT) method with shrimp larvae (Artemia salina Leach). Pyrazoline PF-2OH-4Cl is non-toxic as LC50 260.016 µg/mL, while chalcone   2OHA-4ClBD and pyrazole TFP-2OH-4Cl showed high toxicity with LC50 2.874 and 5.584 µg/mL.